(untitled) (Texas Journal of Agriculture and Biological Sciences, 2026)
Plumeria species are highly valued ornamental and medicinal plants, but their conventional propagation methods are slow and inefficient for large-scale production. This study focuses on the development of a complex biotechnological system for the in vitro propagation of Plumeria plants. The system integrates optimized surface sterilization procedures, nutrient media composition, and plant growth regulators to ensure high regeneration efficiency. Shoot induction, multiplication, rooting, and acclimatization stages were systematically optimized under controlled laboratory conditions. The results demonstrate that the use of Murashige and Skoog (MS) medium supplemented with appropriate concentrations of cytokinins and auxins significantly enhances micropropagation efficiency. The developed protocol ensures rapid, uniform, and disease-free plant production, offering a reliable biotechnological approach for the conservation and mass propagation of Plumeria species